Juridical Analysis of Health Services for Elderly Hajj Pilgrims - Maikel, Mahesa Paranadipa; Syahruddin, Maslim (The Avicenna Medical Journal, 2024)
Indonesia with the largest Muslim population causes the number of Muslims who registered to leave for the holy land to increase, including the number of elderly pilgrims in 1444 H/2023 M as many as 10,166 people from a total quota of 221,000 pilgrims.  The Indonesian Ministry of Religious Affairs issued several special policies related to elderly pilgrims. The program is outlined in the "Elderly Friendly Hajj Guide" which consists of several important things in providing services to elderly pilgrims both at the time of departure, while in the holy land, and when returning to the homeland. This research uses a descriptive qualitative approach and secondary data, in the form of normative research through literature studies consisting of laws and regulations, books, journals, and presentation papers. Regulations related to elderly pilgrims have been stated in Law No. 8 of 2019 on the Implementation of Hajj and Umrah. However, existing laws and regulations have not specifically regulated services for elderly pilgrims, so special regulations are needed that regulate elderly pilgrims including elderly Hajj health services. The Indonesian Ministry of Health in supporting the Elderly Friendly Hajj policy seeks to improve health services to pilgrims, especially to elderly pilgrims. Policy changes related to health istithaah are needed to reduce the risk of morbidity and mortality of elderly pilgrims along with the increasing number of elderly pilgrims in the coming year.